Detection and quantification of Sclerotinia sclerotiorum infestation of canola petals using a clearing and staining technique. Issue 1 (2nd January 2023) - Jayasena, Kithsiri Wimal; van BURGEL, ANDREW; Galloway, Jean; Thomas, Geoff
Abstract: Petal testing can be used to determine the presence of Sclerotinia sclerotiorum inoculum during canola flowering as an indicator of disease risk and the potential need for fungicide application. Traditionally, the culture plate method has been used to test petals, but this takes up to 7 days to obtain results, which is a drawback in terms of making timely fungicide use decisions. Therefore, the availability of a simple, faster detection technique for S. sclerotiorum infected canola petals would be an advantage. We have documented and compared a canola petal clearing and staining technique with the standard culture plate method to study sclerotinia ascospore infestation. The staining technique was found to be a rapid, simple and reliable method compared to the traditional culture plate system.